Postpartum Fatigue: A Critical Challenge for New Mothers - Nastiti, Aria Aulia (Pediomaternal Nursing Journal, 2024)
Postpartum fatigue (PPF) is a pervasive and often underrecognized challenge affecting 45-95% of new mothers. This editorial explores the prevalence, impact, and management of PPF, emphasizing its far-reaching consequences on maternal health, mother-infant bonding, and family dynamics. The article highlights the critical role of nurses in addressing PPF through early identification, education, and support. Key strategies include proactive screening, promoting self-care practices, and advocating for comprehensive postpartum care. The importance of building strong support networks and referring mothers to appropriate specialists is underscored. By recognizing PPF as a serious health concern rather than an inevitable aspect of motherhood, healthcare providers can significantly improve outcomes for new mothers and their families. This piece calls for continued research and the development of patient-centered care strategies to effectively manage postpartum fatigue and support maternal well-being. Keywords: fatigue; maternal health; nurse’s role; postpartum fatigue